Abortion between Islamic provisions and a criminal crime - Naeem, Maad Dhaeer (Journal of Islamic Sciences, 2025)
The main objective of the research (abortion between Islamic provisions and criminal and medical crime) is to put the foundations for these provisions into effect, whether from a legal or medical point of view, and to clarify more of the legal materials that were legised in this regard. We have adopted the triple division of this study labelled (abortion between Islamic provisions and criminal and medical crime), where the study was limited to the analytical method of showing judgements, whether religious, criminal or medical.